Comparing catch efficiency of five models of pot for use in a Newfoundland and Labrador cod fishery. - Phillip Meintzer; Philip Walsh; Brett Favaro (PLoS ONE)
Sustainability of commercial fisheries is best achieved when fishing gears are selective and have low impacts on bottom habitat. Pots (baited traps) are a fishing technology that typically has lower impacts than many other industrial gears. In this study we compared the efficiency of five models of pots (baited traps) designed to catch Atlantic cod (Gadus morhua) for use in Newfoundland and Labrador (NL)'s expanding cod fishery. We compared catch per unit effort (CPUE) and total lengths of cod across each pot type, as well as bycatch rates of each model. All pot types were successful at catching cod, but two models (the modified Newfoundland pot, and a four-entrance pot of our design) had highest CPUE. Specifically, we found that modifying Newfoundland pots increased their CPUE by 145% without a corresponding increase in bycatch. None of the pot types produced substantial amounts of bycatch. This study demonstrated that potting gear is an effective way to catch cod in NL, and that there is flexibility in which pot fishers can use, depending on the layout of their fishing vessel.